PRODUCTIVENESS OF SPECIAL EDUCATION OFFICERS IN NIGERIA ADMINISTRATION - Josephine. D, Nanjwan,; Raymond O, Orgar,; Vitalis U, Eke,; Blessing B, Anam, (International Journal of Psychosocial Rehabilitation, 2020)
This paper is based on the productiveness of special education officers in Nigerian administration. The paper viewed the need for every school to produce a suitable sound curriculum and to determine requirements for students with special needs to be admitted. The appropriate place for special education administration is an issue of concern. The administration of special education is segmented into four levels, namely officers at the federal, state, and local governments and at the institutional levels. Threats confronting special education and its downside were discussed alongside solutions to the difficulties confronted in the administration. It was observed that Nigeria is making a frank effort, though there are a lot of blunders that need corrections.